The Many Faces of a Teacher: Exploring School Teachers’ Experiences with Multiple Responsibilities Amidst Post-Pandemic Times - Jumdani, Evelyn L (PPSDP International Journal of Education, 2024)
This qualitative study aimed to explore the experiences of public elementary school teachers in Carmen District, Davao del Norte, Philippines, in handling multiple responsibilities during the post-pandemic period. Ten teachers were selected as participants using purposive sampling techniques. The study identified four main themes characterizing teachers' experiences: Testing teachers' versatility, Doing countless responsibilities, Excelling amidst trials, and Challenged with Multiple Responsibilities. Additionally, two coping mechanisms emerged from the data: Stress management and One task at a time system. Furthermore, the study uncovered insights related to educational management, including themes such as Work-life balance and Handling Task Conflict Effectively. The findings provide valuable insights into the nuanced challenges faced by public elementary school teachers in the post-pandemic context and offer implications for educational policy and practice.